FAKTOR-FAKTOR YANG MEMPENGARUHI IBU MEMBERIKAN MAKANAN TAMBAHAN PADA BAYI USIA KURANG DARI ENAM BULAN - Juni Setiawan (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2016)
Gives food supplement for baby less than six months great opportunities entry of disease, This is caused by the immune system of infants aged less than six months have not been perfect. The purpose of this study was to determine the factors that affect the mother gives food supplement in infants aged less than six months in sumberanyar Banyuputih situbondo. This research was descriptive research. The population in this study were all breastfeeding mothers who give food supplement in infants aged less than six months in the village sumberanyar amount 125 peoples. Sampling method using random sampling technique amount 56 respondents. The data collection used by questionnaires.The results showed that majority respondents which give food supplement for baby less than six months were low knowledge as 20 respondents (36%), health officials have given the IEC as many as 49 respondents (87.5%), advertisements factor as many as 31 respondents (55%) were affected, social and cultural factors as much as 22 respondents (39%) were affected, educational factors as much as 23 respondents (41%) of primary school graduates, income factor of 30 respondents (53.5%) low income. Keywords: Giving Food Supplement, Baby Less Than Six Months. ABSTRAK Pemberian makanan sebelum bayi berumur enam bulan memberikan peluang besar masuknya berbagai penyakit, hal ini disebabkan sistem imun bayi yang belum sempurna. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi ibu memberikan makanan tambahan pada bayi usia kurang dari enam bulan di Desa Sumberanyar Kecamatan Banyuputih Kabupaten Situbondo. Jenis penelitian ini adalah deskriptif. Populasi penelitian ini adalah semua ibu menyusui yang memberikan makanan tambahan pada bayi usia kurang dari enam bulan sebanyak 125 orang. Metode pengambilan sampel menggunakan tehnik random sampling yakni 56 responden. Pengambilan data dilakukan dengan kuesioner.Hasil penelitian menunjukkan bahwa sebagian besar responden yang memberikan makanan tambahan pada bayi kurang dari enam bulan yaitu dengan pengetahuan rendah 20 responden (36%), telah diberikan KIE sebanyak 49 responden (87,5%), terpengaruh iklan sebanyak 31 responden (55%), terpengaruh sosial budaya sebanyak 22 responden (39%), lulusan SD sebanyak 23 responden (41%), berpendapatan rendah 30 responden (53,5%) Kata kunci: Pemberian makanan tambahan, Bayi Kurang Enam Bulan.